PAPER QUILLING AS AN ARTWORK MEDIA WITH FLORA DECORATIVE IN ART LEARNING FOR VII GRADE STUDENT OF JUNIOR HIGH SCHOOL 1 BAE KUDUS - Pawekas, Restu Angening; Syafii, Syafii; Murtiyoso, Onang (Eduarts: Jurnal Pendidikan Seni, 2019)
The purpose of this study is (1) explain the form of learning flora’s decorative using the quilling techniques on students class VII D SMP Negeri 1 Bae Kudus, (2) explain the results of learning work flora’s decorative using the quilling techniques on students class VII D SMP Negeri 1 Bae Kudus. The study uses an quantitative qualitative approach that is explrative. Data collection techniques used used are observation, intervews, documentation, and test. Based on the results of the research, it may be suggested that flora’s decorative production forms use quilling techniques, consisting of, (1) the learning indicator that refers to the aspect of knowledge , and skill written on the RPP; (2) the learning materials that refer to the aspect of knowledge and skill according to the RPP; (3) the learning strategy of inquiry learning, whereas the method of learning is the method of discourse, demonitation, and an assignment, and (4) the evaluation based on three aspects is the idea-the idea, the visual use of visual aesthetics, and the masterpiece of craftsmanship.Secondly, based on the results on the students from the very aspect of the idea on controlled observation 1 and surveillance 2, the drawing of objects varies in shape and doesn’t only make one object bold 2-3 objects in one image area. Based on visual aesthetic aspects in applying elements and principles of art in accordance with the stages of SMP and experience improvement. Based on technical mastery aspects the average student has experienced improvments in neatness and mastery of basic techniques.